Micropropagation of selected improved materials from Eucalyptus camaldulensis Dehn. for paper production in Erbil, Iraq - Qader, Nozad Ali (2015)
Eucalyptus camaldulensis is one of the most popular multipurpose tree species that had been widely planted in Iraq. Eucalyptus plantations are established in Iraq for many purposes including pulp and paper industry. Generally, industrials harvest these trees at 10-12 years old for paper productions. Since the high demand of its pulp and paper increases yearly, the first part of this study was conducted to find out the possibility of shorten rotation cycle from 10-12 years to 5 years, and to conduct plus tree selection as improved material for micropropagation. However, this was followed by developing micropropagation protocol using material selected from the first part using shoot tips and nodal segments for mass production. In the first part, improved materials were screened through the use of source base on plus tree selection in the field based on good properties. Sixty E. camaldulensis trees (thirty from ten-year-old and thirty from five-year-old stand) were randomly selected through stratified sampling from two plantations in Erbil, northern Iraq. The trees were selected based on the growth performance of both qualitative and quantitative characteristics for fibre morphology and quality parameters. In the phase of property selection, sixteen trees with good ranking scores based on growth performance and fibre morphology were selected from these sources. In the final phase, the selected trees were re-examined according to growth performance, fibre morphology, and cumulative characteristics. As a result, four trees (two 5-year-old trees and two 10- year-old trees) with the highest score were chosen as the sources for micropropagation. In the second part of this study for the micropropagation protocol, surface sterilization protocol of the seeds was established. Therefore, rinsing seeds of four different E. camaldulensis (selected plus trees) with commercial Clorox (25%) for 10-30 minutes was found to be effective. Shoot tips and nodal segment explants obtained from seeds of selected genotype of E. camaldulensis tree, were cultured on MS medium containing seven concentrations of BAP; control 1.0, 1.5, 2.0, 2.5, 3.0, and 3.5mg L-1 in a combinations with 0.1 mg L-1 of NAA and 0.1 mg L-1 of IBA for each concentration of BAP. Shoot induction was achieved from shoot tips and nodal segment explants through direct organogenesis pathway. Parameters used in this study were the number of shoots and shoot length per culture. The best result was achieved using shoot tip explants in MS media, supplemented with 3.0 mg L-1 BAP in combination with 0.1 mg L-1 NAA. The mean number is 9.10 shoots per explant at 11.83 mm length. For shoot elongation, the best result was achieved using half strength of MS medium, supplemented with 1.0 mg L-1 BAP, producing 3.31 cm. The elongated shoots were cultured on half-strength of MS medium for in vitro rooting. The best result was achieved with medium supplemented with 1.5mg L-1 of NAA, producing 9.00 roots with 2.63 cm in length. In the hardening and acclimatisation stage, the plantlets were transferred to polybags containing sand, red soil, and peat moss in the ratio 1:1:1, and was kept under the shade at the nursery. However, 70 % of the plantlets survived after 3 weeks of transplanting into the nursery. In conclusion, based on this study, it was found that there were no significant differences between 5 year-old and 10 year-old trees for paper production. Industrials can harvest Eucalyptus plantations at 5 year-old to reduce the rotation cycle. In addition, a protocol was developed for the micropropagation of superior selected genotype of E. camaldulensis.